Ошмес син: кылбурен роман-малпаськон / Федор Пукроков - Пукроков Федор Пукрокович (Удмуртия, 1984)
Экземпляры: кр (20220520) / Инвентарный номер: 8626 / Авт.знак: П 88 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5